Autonomous mobile robot using myRIO - Yong, Zong Wei (2017)
Current research show that autonomous mobile robot is being widely researched to reduce human work and ease the job. In the research, mobile robot very useful for human because hazards and human limitations have the main reason for the need for more versatile and powerful mobile robots, especially in machining industry and military bases. Besides that, stable design for mobile rohot can easy to move in any environmentaL Moreover, the navigation and obstacle the object also famous used in mobile robot. In this project, the research study is conducted to develop an autonomous mobile robot algorithm with implementation of dynamic modelling using Newton-Euler approach. The rigid body of the mobile robot is equipped with two wheels and a castor for the purpose of simple control and stable balancing. In addition, Kinect motion sensor will be applied for the image detection and video recording while ultrasonic sensor obstacle avoidance of the mobile robot. On the other hand, the simulation of the control mechanism is realized through Lab VIEW software package where the development of the mobile robot environment is carried out and transferred to National Instrument myRIO hardware. Results found that the autonomous mobile robot successfully obstacle and record video while using both sensors. It is believed that this mobile robot can used in hazards environment to record all the important data that need those environment.